Medal upamiętniający zawarcie związku małżeńskiego między Teresą Kunegudną Sobieską a Maksymilanem Emanuelem Wittelsbachem z 1694 roku, autorstwa Georga Haustscha. Próba interpretacji na przykładzie wybranych dzieł sztuki (medalierstwa i grafiki) - Rokita, Jan Gustaw (Studia Europaea Gnesnensia, 2018)
In the article, the author describes in detail two selected pieces of art which bear considerable resemblance to the medal minted by Georg Hautsch. As the author observes, no representation in the entire painterly and graphic legacy of associated with Jan III Sobieski offers a direct prototype on which the medallist may have relied. It should therefore be suspected that the royal likeness on the obverse was based on several earlier representations in graphic arts or constituted an original project by Hautsch.